2011
DOI: 10.1002/hep.24376
|View full text |Cite
|
Sign up to set email alerts
|

Endpoints and clinical trial design for nonalcoholic steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease in the general population. Nonalcoholic steatohepatitis (NASH), the aggressive form of NAFLD, is associated with an increased risk of liver-related mortality and cardiovascular disease. Currently, a liver biopsy is the only generally acceptable method for the diagnosis of NASH and to assess its progression towards cirrhosis. While several treatments have shown evidence of efficacy in clinical trials of varying design, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
634
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 687 publications
(662 citation statements)
references
References 58 publications
(83 reference statements)
6
634
0
9
Order By: Relevance
“…A nonsmoker was defined as an individual who had never smoked or who had smoked fewer than 100 cigarettes in his or her life. Positive alcoholic history was defined as alcohol consumption over 30 g/day for male patients and 20 g/day for female patients when converted to ethanol 35. Cirrhosis was diagnosed mainly by a histopathological examination (82% for patients with HBV‐HCC, 77% for HCV‐HCC, and 74% for NBNC‐HCC).…”
Section: Methodsmentioning
confidence: 99%
“…A nonsmoker was defined as an individual who had never smoked or who had smoked fewer than 100 cigarettes in his or her life. Positive alcoholic history was defined as alcohol consumption over 30 g/day for male patients and 20 g/day for female patients when converted to ethanol 35. Cirrhosis was diagnosed mainly by a histopathological examination (82% for patients with HBV‐HCC, 77% for HCV‐HCC, and 74% for NBNC‐HCC).…”
Section: Methodsmentioning
confidence: 99%
“…However, the precise definition of significant alcohol consumption in patients with suspected NAFLD is uncertain. A recent consensus meeting 58 concluded that, for NASH clinical trials candidate eligibility purposes, significant alcohol consumption be defined as >21 drinks per week in men and >14 drinks per week in women over a 2-year period prior to baseline liver histology. Furthermore, this group recommended that validated questionnaires should be used to quantify the amount of alcohol consumption in the context of clinical trials.…”
Section: Natural Historymentioning
confidence: 99%
“…As the US population ages and becomes more obese, the prevalence of NAFLD will continue to increase, and NAFLD will become the most important cause of chronic liver disease. 9 Although the results of a recent study using vitamin E treatment for NASH are promising, 4 it is unlikely that the problems with NAFLD will be resolved with medication alone. The management of NAFLD is currently limited to weight reduction by means of diet and exercise and to treatment of the individual components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent controlled trial, vitamin E therapy, as compared with placebo, was associated with a significantly higher rate of improvement in NASH. 4 The clinical significance of this finding has not been determined, and long-term effects of this therapy have not been studied.…”
mentioning
confidence: 99%